Risk factors of Charcot Neuroarthropathy Development in Patients with Type 2 Diabetes - Nehring, P.; Mrozikiewicz-Rakowska, B.; Maroszek, P.; Sobczyk-Kopcioł, A.; Krzyżewska, M.; Płoski, R.; Karnafel, W. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Charcot neuroarthropathy is a very rare form of diabetic foot syndrome occurring among others in patients with diabetes mellitus. Charcot neuroarthropathy leads to bone tissue destruction and may result in foot amputation. The aim of the study was to identify risk factors of Charcot neuroarthropathy occurrence in patients with diabetic foot and type 2 diabetes.The study included 144 patients with type 2 diabetes; 33 with Charcot neuroarthropathy and 111 with diabetic foot of neuropathic origin without neuroarthropathy. The study was perform in Gastroenterology and Metabolic Diseases Department, Medical University of Warsaw, Poland.The regression analysis showed that Charcot neuroarthropathy occurrence risk factors were: male gender (OR=4.94, 95% CI:1.63–15.03, p=0.003), age (OR=0.92, 95% CI:0.87–0.96, p=0.0001), diabetic foot duration (OR=1.19, 95% CI:1.08–1.32, p=0.00002) and height (OR=1.078, 95% CI:1.019–1.140, p=0.007). A positive effect on Charcot neuroarthropathy presence was exerted by body weight (OR=1.027, 95% CI:1.003–1.051, p=0.03) and hips circumference (OR=1.034, 95% CI:0.997–1.072, p=0.04).The existence of the specific factors influencing Charcot neuroarthropathy development may result in earlier identification of patients at risk of its development. There is a necessity to take special care for patients prone to develop Charcot neuroarthropathy in order to prevent its occurrence and severe complications.
Keywords: neuropathy; obesity; peripheral arterial disease